Glio-vascular modifications caused by Aquaporin-4 deletion in the mouse retina. (May 2016) - Nicchia, Grazia Paola; Pisani, Francesco; Simone, Laura; Cibelli, Antonio; Mola, Maria Grazia; Dal Monte, Massimo; Frigeri, Antonio; Bagnoli, Paola; Svelto, Maria
Abstract: Aquaporin-4 (AQP4) is the Central Nervous System water channel highly expressed at the perivascular glial domain. In the retina, two types of AQP4 expressing glial cells take part in the blood-retinal barrier (BRB), astrocytes and Müller cells. The aim of the present study is to investigate the effect of AQP4 deletion on the retinal vasculature by looking at typical pathological hallmark such as BRB dysfunction and gliotic condition. AQP4 dependent BRB properties were evaluated by measuring the number of extravasations in WT and AQP4 KO retinas by Evans blue injection assay. AQP4 deletion did not affect the retinal vasculature, as assessed by Isolectin B4 staining, but caused BRB impairment to the deep plexus capillaries while the superficial and intermediate capillaries were not compromised. To investigate for gliotic responses caused by AQP4 deletion, Müller cells and astrocytes were analysed by immunofluorescence and western blot, using the Müller cell marker Glutamine Synthetase (GS) and the astrocyte marker GFAP. While GS expression was not altered in AQP4 KO retinas, a strong GFAP upregulation was found at the level of AQP4 KO astrocytes at the superficial plexus and not at Müller cells at the intermediate and deep plexi. These data, together with the upregulation of inflammatory markers (TNF-α, IL-6, IL-1β and ICAM-1) in AQP4 KO retinas indicated AQP4 deletion as responsible for a gliotic phenotype. Interestingly, no GFAP altered expression was found in AQP4 siRNA treated astrocyte primary cultures. All together these results indicate that AQP4 deletion is directly responsible for BRB dysfunction and gliotic condition in the mouse retina. The selective activation of glial cells at the primary plexus suggests that different regulatory elements control the reaction of astrocytes and Müller cells. Finally, GFAP upregulation is strictly linked to gliovascular crosstalk, as it is absent in astrocytes in culture. This study is useful to understand the role of AQP4 in the perivascular domain in the retina and its possible implications in the pathogenesis of retinal vascular diseases and of Neuromyelitis Optica, a human disease characterized by anti-AQP4 auto-antibodies. Graphical abstract: Highlights: AQP4 is important in maintaining the BRB integrity at the deep plexus. AQP4 deletion causes an inflammatory response and a reactive phenotype restricted to astrocytes at the superficial plexus. The astrocyte reaction is strictly linked to gliovascular crosstalk. Differential regulatory elements are involved in activation of astrocytes and Muller cells.